2006
DOI: 10.1111/j.1365-2729.2006.00171.x
|View full text |Cite
|
Sign up to set email alerts
|

A community of practice approach to the development of non‐traditional learners through networked learning

Abstract: This paper analyses a sample of online discussions to evaluate the development of adult learners as reflective practitioners within a networked learning community. The context for our study is a blended learning course offering post-experience professional training to nontraditional university students. These students are parents and carers of people with autistic spectrum disorder (ASD). We use Lave and Wenger's 'communities of practice' as a theoretical framework for establishing how students develop a learn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 14 publications
1
23
0
5
Order By: Relevance
“…Theory verification was also evident in the final group of 17 studies that we identified for our guiding question 3. In this group, we found six studies showing this trend: Evans, Yeung, Markoulakis, and Guilcher (2014), Gray (2004), Guldberg and Pilkington (2006), Moule (2006), Rogers (2000), and Brosnan and Burgess (2003). The aims of the first five studies coincided: Each sought to understand the extent or the nature of CoP formulation in the online learning environment.…”
Section: Guiding Questionmentioning
confidence: 99%
See 3 more Smart Citations
“…Theory verification was also evident in the final group of 17 studies that we identified for our guiding question 3. In this group, we found six studies showing this trend: Evans, Yeung, Markoulakis, and Guilcher (2014), Gray (2004), Guldberg and Pilkington (2006), Moule (2006), Rogers (2000), and Brosnan and Burgess (2003). The aims of the first five studies coincided: Each sought to understand the extent or the nature of CoP formulation in the online learning environment.…”
Section: Guiding Questionmentioning
confidence: 99%
“…Among these, two studies (Correia & Davis, 2008;Guldberg & Pilkington, 2006) stood out because, before the actual analysis, they identified a need for acknowledging how different dynamics lead to different types of communities. To illustrate this point, both studies drew on Henri and Pudelko's (2008) classification of four levels of communities: communities of interest; goal oriented communities; a learner's community; and communities of practice.…”
Section: Formation Of a Cop Versus Formation Of Different Types Of Comentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, Guldberg and Pilkington (2006) attempted to establish how participants developed a "learning community based upon mutual engagement, joint enterprise and shared repertoires" and the resulting "changes in the quality of collaborative activity over time … with different subsets [of students] sharing and coconstructing common understandings" (p. 159).…”
Section: Lessons From the Researchmentioning
confidence: 99%